The MDAB students' reading attitudes and their academic reading performance / Affidah Morni … [et al.] - Morni, Affidah; Alfred Tom, Amelia; Mohd Nawawi, Norlida; Wan Hassan, Sharifah Zakiah (Research Management Institute (RMI), 2013)
Reading is a very important factor in enriching one's knowledge and in widening one's perspective. However, the Malaysian reading scenario does not reflect an impressive reading culture as society seems to be greatly ambivalent about reading. Ganakumaran (2004) revealed that many Malaysians are 'struggling readers'. By this, he referred to those who have minimal confidence in their ability to read and minimal sense of themselves as readers. Meanwhile, struggling readers according to Vacca and Vacca (1999) are those students who are low achievers. They lack cognitive competencies which may include reading comprehension, study skills, word recognition and reading fluency. On the other hand, Wigfield, Eccles and Rodriguez (1998) believed that struggling readers are notably unmotivated. They are especially likely to have low confidence in their reading, which is termed self-efficacy in the research literature. Reading becomes necessary only when the students need to sit for exams and get excellent grades. In fact, not many Malaysians are able to find reading exciting because they have had bad experiences with reading. One of the reasons has very much to do with the reading material itself. This is because they have not connected with texts that are pleasurable to read. Malachi (2002) also pointed out that students tend to perceive reading as laborious and tedious. Some of them get turned off from reading because they have difficulties coping with complex texts. They feel 'burdened' when they have to refer to the dictionary and guess the meanings of the words all the time through the process of reading. When the reading material is inappropriate as it is not at the students' level of competence or area of interest, they will find it difficult to connect and enjoy the text.